Acute onset of inflammatory colitis in overlap with psoriatic arthritis and systemic lupus erythematosus following treatment with secukinumab. Issue 4 (2021) - Almer, Sven; Faustini, Francesca; Szczegielniak, Sylwester
No abstract available